2012
DOI: 10.1021/la3019887
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Distribution of Anionic Phospholipids in Supported Lipid Bilayers

Abstract: Lipid bilayers with a controlled content of anionic lipids are a prerequisite for the quantitative study of hydrophobic-electrostatic interactions of proteins with lipid bilayers. Here, the asymmetric distribution of zwitterionic and anionic lipids in supported lipid bilayers is studied by neutron reflectometry. We prepare POPC/POPS (3:1) unilamellar vesicles in a high-salt-concentration buffer. Initially, no fusion of the vesicles to a SiO(2) surface is observed over hours and days. Once the isotonic buffer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…Recent studies showed unique substrate-induced phenomena of SLBs, which do not occur in the free-standing membranes; for example, decoupled phase transition [34,35,36,37] and asymmetric molecular distribution between the upper and lower leaflet of a SLB [38,39,40]. Understanding the interaction between solid substrates and lipid bilayers are important to realize artificial cell membrane systems on functional solid devices avoiding the denaturing of lipids and proteins and, furthermore, to control the bilayer membranes with functional substrates, because cell membranes are laterally heterogeneous and vertically asymmetric.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed unique substrate-induced phenomena of SLBs, which do not occur in the free-standing membranes; for example, decoupled phase transition [34,35,36,37] and asymmetric molecular distribution between the upper and lower leaflet of a SLB [38,39,40]. Understanding the interaction between solid substrates and lipid bilayers are important to realize artificial cell membrane systems on functional solid devices avoiding the denaturing of lipids and proteins and, furthermore, to control the bilayer membranes with functional substrates, because cell membranes are laterally heterogeneous and vertically asymmetric.…”
Section: Introductionmentioning
confidence: 99%
“…48 Lipid asymmetry between the two leaflets in mixed bilayer systems was recently reported for bilayers deposited by osmotic shock from 3:1 POPC/POPS vesicles where the initial vesicle adsorption took place in buffer solutions containing 1.1 M NaCl. 49 For the bilayers in Figure 4, simultaneous fitting of the SLD values in the inner and outer Table 1 (fitting parameters in Table S1 of the Supporting Information). The reflectivity was measured for three degrees of solvent deuteration: D 2 O (red circles, top curve), CMSi (green triangles, bottom curve), and H 2 O (blue squares, middle curve).…”
mentioning
confidence: 99%
“…The local environments of bilayer leaflets frequently differ: examples include the different leaflet solvent environments in vivo, or preferential substrate interactions with one species [5,[21][22][23]. The simplest effects can be modelled with an excess free energy per lipid −ζ for findAll rights reserved.…”
Section: Effect Of An External Fieldmentioning
confidence: 99%